A novel offset functions design for five-level h-bridge NPC inverters to reduce switching loss - Quach Thanh Hai; Do Duc Tri; Phan Thanh Minh; Danh Tuan Le; Duong Tran Dinh Thao (Journal of Technical Education Science, 2017)
This paper presents a new carrier pulse width modulator algorithm to reduce switching loss in five-level H-bridge neutral point clamped inverter. The proposed technique is based on the offset function being 3rd harmonic voltage. The offset voltage will be added to the control voltages so that the voltage of phase which has absolute of load current largest move into top (or bottom) of the carriers. So reducing the intersection of control voltage in that phase and the carriers and then reducing the number of switching losses. With the pulse width modulation method and flexible offset voltages in this study, switching loss in a cycle will be decrease. Simulation results will be provides in order to validate the proposed algorithm.